The Eye as a Window to Systemic Hemodynamics: A Novel Approach to Estimating Central Venous Pressure via Tonometry in Sepsis - M. Irvan Noorrahman; Nopian Hidayat; Riki Sukiandra; Pratama Ananda (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Effective hemodynamic management in sepsis is critical, yet current practices are constrained by the risks and interpretive challenges of invasive central venous pressure (CVP) monitoring. The clinical utility of CVP is debated, fueling the search for safer alternatives. This study investigates a novel approach, exploring intraocular pressure (IOP) as a non-invasive surrogate for CVP, predicated on the direct anatomical link between the ocular venous drainage system and the central circulation. Methods: We conducted a prospective, single-center observational study in a tertiary intensive care unit, enrolling 20 adult patients with sepsis and indwelling central venous catheters. High-fidelity measurements of CVP via a pressure transducer and IOP via Perkins applanation tonometry were performed simultaneously. Data were collected at a baseline steady-state and again 15 minutes after a standardized fluid challenge (median volume 300 mL) to assess the dynamic relationship. The association was quantified using Pearson correlation and modeled with simple linear regression. Results: A strong, statistically significant positive correlation was observed between CVP and IOP at baseline (r=0.756, p=0.001). This physiological coherence was profoundly amplified following the fluid challenge, strengthening to a very strong correlation (r=0.947, p<0.001). The post-challenge data yielded a robust, preliminary predictive model, defined by the equation: CVP (mmHg) = -0.619 + (0.522 x IOP (mmHg)). The slope of this relationship was precisely estimated (95% CI: 0.435 to 0.609). The model demonstrated high predictive power, with post-challenge IOP accounting for 89% of the variance in CVP (R²=0.89). Conclusion: This pilot investigation provides compelling evidence for a strong and dynamic correlation between IOP and CVP in critically ill patients with sepsis. The findings suggest that ocular tonometry shows significant promise as a non-invasive method for assessing right-sided filling pressures and, more importantly, for tracking the dynamic response to fluid therapy, thereby offering a potential window into venous congestion. While intriguing, these results are from a small cohort. The derived formula is strictly hypothesis-generating and requires extensive validation in larger, more diverse clinical trials before any potential for clinical application can be considered.